Relationship Between Vertical Jump, Linear Sprint and Change of Direction in Chilean Female Soccer Players - Aedo-Munoz, E; Merino-Munoz, P (Editura Universitatii din Pitesti, 2021)
Objective: To establish associations between physical performance indicators in two series of a Chilean women s soccer team and to know the differences between them. Method: 29 players from a Chilean first division team (Adult = 12 and Sub-17 = 19). Countermovement jump (CMJ), linear sprint 10 (T10) and 30 meters (T30) time, change of direction 180° (COD180°) and change of direction deficit (CODD), in the preparatory period were evaluated. Pearson correlation coefficient (r) tests were performed to determine associations between physical tests and magnitude-based inferences to determine differences between categories. Results: Strong negative correlations (p<0.05) were found between CMJ with T10 and T30 (r =-0.72 and-0.77 respectively) and moderate with COD180° (r =-0.49). T10 had a strong positive correlation with T30 (r = 0.88) and moderate with COD180° (r = 0.59). T30 had a moderate positive correlation with COD180° (r = 0.54) and finally CODD only had a correlation with COD180° (r = 0.75). Likely differences were found between CMJ, COD180° and CODD (Standardized Difference = 0.60, 0.68 and 0.70 respectively) in favor of the adult category. There were unclear differences at T10 and T30. Conclusion: From our results, we can conclude that there is an association between CMJ, T10, T30 and COD180° However, for CODD, they were not found with CMJ, T10 and T30, so it is recommended that coaches who work with female soccer players apply specific tests to measure these capabilities, and also try to match the total path of the change of direction test with one of the linear speed tests, so they can also know the CODD of their athletes. © JPES.